2016
DOI: 10.1097/jsm.0000000000000263
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain in Young Basketball and Floorball Players

Abstract: The study attested that LBP is a relatively common complaint in young team sport players. Targeted measures to examine causes, risk factors, and prevention of LBP in youth sports are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 28 publications
6
44
0
1
Order By: Relevance
“…In fact, in the baseline questionnaire, the players were asked about any low back complaints and 53% of the players reported low back pain during the preceding 12 months. In addition, in our previous cross‐sectional study, we found an annual prevalence of any back pain as high as 44% in basketball players and 62% in floorball players, which is in line with previous studies . Van Hilst et al found the prevalence of LBP to be 54%‐66% in young speed skaters, 33%‐64% in field hockey players and 64% in football players.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In fact, in the baseline questionnaire, the players were asked about any low back complaints and 53% of the players reported low back pain during the preceding 12 months. In addition, in our previous cross‐sectional study, we found an annual prevalence of any back pain as high as 44% in basketball players and 62% in floorball players, which is in line with previous studies . Van Hilst et al found the prevalence of LBP to be 54%‐66% in young speed skaters, 33%‐64% in field hockey players and 64% in football players.…”
Section: Discussionsupporting
confidence: 91%
“…In floorball, the playing position also often includes trunk flexion and rotation and asymmetrical positions due to the use of a stick. According to our previous report, annual prevalence of LBP in young basketball and floorball players ranges from 44% up to 62% …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on floorball injuries have focused on the national level. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] These investigations have shown that most of the acute injuries in floorball affect the ankle and knee, 2-7 whereas overuse injuries involve most commonly leg/calf, knee and lower back. 5 8-10 Severe knee ligament injuries, such as ruptures of the ACL, have proven to be a concern in floorball national leagues, specifically among female players.…”
Section: Key Messagesmentioning
confidence: 99%
“…The interest in epidemiology and prevention of overuse injuries has increased during the past few years [2, 10,15,36,38,46]. Team sports, especially those involving frequent jumping, throwing or hitting [9,11,27,31,38,66], have been associated with high prevalence of various overuse conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Junge et al [25] reported that overuse knee injuries were the most common injury type in children's (ages 8-15 years) basketball. In addition, one retrospective [29] and one cross-sectional study [46] have attested that overuse injuries affecting the knee and lower back are relatively common complaints among young basketball and floorball players. However, prospective studies are needed to confirm these findings.…”
Section: Introductionmentioning
confidence: 99%